1995
DOI: 10.1111/j.1365-2982.1995.tb00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that enteric motility reflexes can be initiated through entirely intrinsic mechanisms in the guinea‐pig small intestine

Abstract: Although motility reflexes can be elicited in the intestine in vivo after all neural connections with the central nervous system are cut, or in vitro in isolated intestinal segments, it is not proven that the cell bodies of the primary sensory neurons for these reflexes are in the intestinal wall. It is feasible that the nerve cells are in dorsal root ganglia and that axon reflexes are involved in the initiation of the reflexes. We have examined reflexes in segments of guinea-pig intestine in which extrinsic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
6

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 26 publications
2
46
0
6
Order By: Relevance
“…Several previous studies have shown that there are intrinsic sensory neurons in the intestine (Langley and Magnus 1905;Crema et al 1970;Furness et al 1995). They have been identiWed in the small intestine of the guinea-pig as Dogiel type II neurons (Kirchgessner et al 1992;Kunze et al 1995;Bertrand et al 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies have shown that there are intrinsic sensory neurons in the intestine (Langley and Magnus 1905;Crema et al 1970;Furness et al 1995). They have been identiWed in the small intestine of the guinea-pig as Dogiel type II neurons (Kirchgessner et al 1992;Kunze et al 1995;Bertrand et al 1997).…”
Section: Discussionmentioning
confidence: 98%
“…However, reflexes initiated by mechanical stimuli applied to the mucosa are unaffected, indicating that mucosal mechanoreceptors have cell bodies within the wall of the intestine. In the guinea-pig ileum, motility reflexes elicited by mucosal deformation and muscle stretch persist after all neural connections with the CNS have been severed and degenerated (Furness et al 1995a) and it appears that the cell bodies of the mucosal mechanoreceptors are located in the sub-mucous plexus (Kirchgessner et al 1992) and those of the chemosensory neurons in the myenteric plexus . The primary sensory neurons have been identified as those neurons with AH (after-hyperpolarising) electrophysiological characteristics and Dogiel type II morphology ).…”
Section: B) Intrinsic Sensory Neurons and Interneuronsmentioning
confidence: 97%
“…In the small intestine of the guinea-pig, inhibitory motor neurons to the circular muscle have the chemical code NOS/VIP±NPY (Costa et al 1992a;Furness et al 1995a;Brookes 1993;Furness et al 1995b). In the mouse, the presence of terminals in the circular muscle layer with similar combinations of markers to that observed in myenteric cell bodies, suggests that, as in other species, many of the NOS/VIP±NPY neurons in the small intestine and NOS/VIP neurons in the large intestine are inhibitory motor neurons to the circular muscle, and hence it is possible that nitric oxide and/or VIP contribute to the nerve-mediated relaxation in the mouse.…”
Section: A) Putative Circular and Longitudinal Muscle Motor Neuronsmentioning
confidence: 99%
“…It could be postulated that axon reflexes in the enteric processes of spinal primary afferent neurons were responsible for initiating the activity observed in the Dogiel type II neurons. However, it has been shown that enteric reflexes in response to muscle stretch are not diminished after the axons of spinal primary afferent neurons have been cut and allowed to degenerate (Furness, Johnson, Pompolo & Bornstein, 1995). Moreover, this interpretation would require transmission from the spinal primary afferent neurons to the processes of the Dogiel type II neurons.…”
Section: Mechanism Of Detection Of Stretchmentioning
confidence: 99%